First report of Heterodera glycines lchinohe on soybean in Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
The soybean cyst nematode (SCN) Heterodera glycines was found inthree soybean fields near Pavia (ltaly) during the summer 2000. This quarantinenematode was not known in Italy. The soybean plants were smaller, with "yellowdraft" disease, the roots were poorly developed and without or with few nitrogennodules. The population of SCN found was well established, and all stages wererecorded. Adult females and juveniles of H. glycines had high abundance. Anaverage of 59.5 cysts for 100 cm3 soil were recorded disease. The density ofpopulation ranged from 7900 to 19200 SCN eggs/100 cm3 soil. This recordhighlights a probable permanent establishment of this plant parasitic nematode inNorth ltaly.
Keywords: Heterodera glycines; soybean; yellow draft; Italy